(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This article is the result of the biostratigraphic studies of the Oligocene-Early Miocene sediments of the foothills of the Kuljuktau Ridge and adjacent territories.The need to dismember the Oligocene-Early Miocene of this territory of the Central Kyzylkum is dictated by the fact that the current state of the validity of the dismemberment and correlation does not provide the necessary accuracy and adequacy of the correlation with the International Stratigraphic Scale.